Impact of Galactic magnetic field modeling on searches of point sources via ultrahigh energy cosmic ray-neutrino correlations - Carpio Dumler, José Alonso (2016)
We apply the Jansson-Farrar JF12 magnetic field model in the context of point source searches by correlating the Telescope Array ultrahigh energy cosmic ray data and the IceCube-40 neutrino candidates, as well as other magnetic field hypotheses. Our field hypotheses are: no magnetic field, the JF12 field considering only the regular component, the JF12 full magnetic field, which is a combination of regular and random field components, and the standard turbulent magnetic field used in previous correlation analyses. As expected from a neutrino sample such as IceCube-40, consistent with atmospheric neutrinos, we have found no significant correlation signal in all the cases. Therefore, this paper is mainly devoted to the comparison of the effect of the different magnetic field hypotheses on the minimum neutrino source flux strength required for a 5σ discovery and the derived 90% C.L. upper limits. We also incorporate in our comparison the cases of different power law indices α= 2.2, α=2.5 for the neutrino point source flux. The differences in the 5σ discovery flux for our magnetic field hypotheses is ∼1%–50%, being the maximum difference with the regular JF12 field and standard turbulent field models, being the standard turbulent higher than the regular one, while the minimum is between the no magnetic field and regular JF12 field. Considering the current flux upper limits, we find that IceCube requires a lifetime ≳5 years to observe neutrino-UHECR correlation signals. Our analysis for different power law indices yielded the same relative behavior between different magnetic field models.